Early Discovery of Children With Lysosomal Acid Lipase Deficiency With the Universal Familial Hypercholesterolemia Screening Program - Sustar, Ursa; Groselj, Urh; Trebusak Podkrajsek, Katarina; Mlinaric, Matej; Kovac, Jernej; Thaler, Martin; Drole Torkar, Ana; Skarlovnik, Ajda; Battelino, Tadej; Hovnik, Tinka (Frontiers in Genetics, 2022)
Lysosomal acid lipase deficiency (LAL-D) is an autosomal recessive lysosomal storage disorder, caused by homozygous or compound heterozygous pathogenic variants in the LIPA gene. Clinically, LAL-D is under- and misdiagnosed, due to similar clinical and laboratory findings with other cholesterol or liver misfunctions. As a part of the Slovenian universal familial hypercholesterolemia (FH) screening LAL-D is screened as a secondary condition among other rare dyslipidemias manifesting with hypercholesterolemia. Out of 669 children included, three were positive for a homozygous disease-causing splicing variant NM_000235.4: c.894G>A (NP_000226.2:p. Gln298Gln) in the LIPA gene (NG_008194.1). The mean age by the diagnosis of LAL-D was 9.8 ± 0.9 years. Moreover, all three LAL-D positive children had an important elevation of transaminases and decreased activity of the lysosomal acid lipase enzyme. Abdominal MRI in all children detected an enlarged liver but a normal-sized spleen. In conclusion, universal FH screening algorithms with confirmatory genetic analysis in the paediatric population enable also rare dyslipidaemia detection at an early age. An important clinical criterion for differentiation between FH and LAL-D positive children is elevated trans-aminase levels (AST, ALT). In all three LAL-D positive children, an improvement in cholesterol and transaminase levels and steatosis of the liver has been seen after early treatment initiation.